PERSEPSI MAHASISWA TERHADAP PERANAN DOSEN PENASEHAT AKADEMIK DI PRODI PKK FPP UNP - mutia indah Meliska; Ernawati . (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
ABSTRACT This research discusses the alertness of the studentsin agreement with academic advisors for academic guidance given 2 out of 5 indicators,namely : fillingout study plan cards, and changing courses. The population study was 457 students. Sampling methods is the proporsional random sampling.The sample of this research was 92 students. Techniques for collecting data using a questionnaire. Data were analyzed throught descriptive analysis with the method of the categorizing assessment based on the average score and assessment percentage. The result of the research concluded that respondents’ level of the achievement in the indicators 1) filling out the study plan cards 68,45% stated quite well, and 2) changes in the course 66,12% stated fairly well. Keywords:The role ofacademic advisors, academic guidance